Analysis of 1000-meter run in Sportyjoy Club athletes in Cimahi City: A biomechanical sports perspective - Erlangga, Yana; Gumilar, Agus; Salman, Salman; Choirunnisa, Jihan (JUMORA: Jurnal Moderasi Olahraga, 2024)
The importance of understanding biomechanics in sports, particularly in running activities, significantly contributes to improving athletes' techniques and performance. This study aims to analyze the 1000-meter running motion of athletes from the Sportyjoy Club in Cimahi City through a sports biomechanics review. The study employs a descriptive analytical method with a one-shot case study design. Kinematic data were obtained from video recordings analyzed using Kinovea software (version 2023.2.1). The study sample comprised 10 middle-distance athletes aged 11–14 years selected through purposive sampling. The results showed that the athletes' average running speed was 3.88 ± 0.68 m/s, with a maximum speed of 5.00 m/s and a minimum speed of 2.87 m/s. The average stance phase duration was 0.21 ± 0.05 seconds, while the swing phase lasted an average of 0.32 ± 0.09 seconds. Biomechanical parameters such as arm flexion angle (57.25 ± 9.69⁰) and knee height (0.45 ± 0.06 m) were also analyzed to evaluate running efficiency. Based on physical fitness assessments, 2 athletes were categorized as very good, 4 as good, 1 as fairly good, and 3 as poor. This study demonstrates that running efficiency is influenced by the stance and swing phases, arm flexion angles, and knee height. Therefore, coaches and athletes can use these findings to improve running techniques, enhance performance, and reduce injury risk through a biomechanical approach